The Halloween effect in European equity mutual funds - Curto, J. D. (2019)
We extend the evidence on the Halloween effect (returns during the months of May to October tend to be lower than returns during the months of November to April) in stock markets by examining the return pattern of 145 European Equity Mutual Funds from 1997 to 2013. The main purpose is to investigate if previously predictabilities in equity stock markets returns are reflected in mutual funds. We conclude that (i) the Halloween effect is statistically and economically significant; (ii) this effect has disappeared after the Bouman and Jacobsen (2002) publication; (iii) an investment strategy based on this anomaly clearly beats the buy-and-hold strategy.